Optimizing Brand Image as Marketing Management of Islamic Private Schools: Optimalisasi Brand Image sebagai Manajemen Pemasaran Sekolah Swasta Islam - A’yuni, Qurnia; Fauji, Imam (Indonesian Journal of Innovation Studies, 2026)
General Background: Islamic private schools require strategic marketing management to establish a distinctive and trusted institutional identity. Specific Background: Brand image at SD Muhammadiyah 1 Candi Labschool Umsida is developed through Islamic values and school-based programs. Knowledge Gap: Previous studies have not examined in depth the integration of Islamic values into brand image optimization as a marketing management strategy. Aims: This study analyzes brand image optimization and its outcomes for the school. Results: A descriptive qualitative approach identified five practices: superior accreditation, inclusive schooling, Islamic character building, circular school, and infrastructure facilities, accompanied by increased student enrollment and parental trust. Novelty: The study integrates Islamic values across multiple branding practices within school marketing management. Implications: The findings provide a context-specific reference for Islamic private schools seeking to manage brand image through coordinated educational programs and communication. Key Findings Highlights Superior accreditation is communicated through benchmarking, digital promotion, and parent testimonials. Inclusive education and Islamic character programs form distinctive institutional practices. Enrollment growth and stronger parental trust emerge as major outcomes of the branding strategy. Keywords: Brand Image, Marketing Management, Islamic Private School, Islamic Values, School Branding